Impact of Online Learning and Utilization of Websites as Learning Media on the Development of Social Interaction for Students of Economic Education Study Program Stambuk 2017 Universitas HKBP Nommensen Medan FY 2021/2022 - Halawa, Tati Octaviani; Pardede, Surya Darma (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to determine the impact of online learning and the use of websites as learning media on the development of social interaction of students of the 2017 Economics Education Study Program, HKBP Nommensen University, Medan in the 2021/2022 academic year. This type of research is a type of survey research with a quantitative approach. The population in this study were all students of 2017 University HKBP Nommensen Medan. The analytical method used in this study is the normality test of multicollinearity test, multiple linear regression analysis, partial t hypothesis test, and simultaneous hypothesis testing (f). The results showed that online learning and the use of websites as learning media had a positive and significant effect on the development of student social interactions which showed that the value of fcount > ftable was 14. 865 > 3.28 and a significant value of 0.00 < 0.05. Based on the results of the f test, it can be concluded that online learning and the use of websites as learning media together have a positive and significant impact on the development of social interaction of students of the 2017 Economics Education Study Program, University of HKBP Nommensen Medan for the 2021/2022 academic year.